The health impact of living in a nursing home with a predominantly different spoken language - Batista, Ricardo; Prud’homme, Denis; Hsu, Amy T.; Guérin, Eva; Bouchard, Louise; Rhodes, Emily; Talarico, Robert; Desaulniers, Jacinthe; Manuel, Douglas; Tanuseputro, Peter (Journal of the American Medical Directors Association, 2019)
Abundant research shows that linguistic barriers can have a negative impact on access to and quality of health care, as well as a patient's health outcomes.1–3 Establishing a culturally appropriate environment, by providing care to nursing home residents in their preferred language, is key in providing good-quality long-term care (LTC) services.4,5 French is one of Canada's 2 official languages. In Ontario, Canada, studies using population-based data have shown that Francophones have a lower perception of good health, higher prevalence of chronic diseases, and greater dependency on LTC services compared to Anglophones.6,7 However, the impact of language discordance on the outcomes of residents in nursing homes has not been previously explored.

Quality and safety in long-term care in Ontario: The impact of language discordance - Batista, Ricardo; Prud'homme, Denis; Rhodes, Emily; Hsu, Amy; Talarico, Robert; Reaume, Michael; Guérin, Eva; Bouchard, Louise; Desaulniers, Jacinthe; Manuel, Douglas; Tanuseputro, Peter (Journal of the American Medical Directors Association, 2021)
Objectives This study compared quality indicators across linguistic groups and sought to determine whether disparities are influenced by resident-facility language discordance in long-term care. Design Population-based retrospective cohort study using linked databases. Setting and Participants Retrospective cohort of newly admitted residents of long-term care facilities in Ontario, Canada, between 2010 and 2016 (N=47,727). Individual residents' information was obtained from the Resident Assessment Instrument Minimum Data Set (RAI-MDS) to determine resident's primary language, clinical characteristics, and health care indicators. Measures Main covariates of interest were primary language of the resident and predominant language of the long-term care facility, which was determined using the French designation status as defined in the French Language Services Act. Primary outcomes were a set of quality and safety indicators related to long-term care: worsening of depression, falls, moderate-severe pain, use of antipsychotic medication, and physical restraints. Multivariable logistic regression models were used to assess the impact of resident's primary language, facility language, and resident-facility language discordance on each quality indicator. Results Overall, there were few differences between francophones and anglophones for quality and safety indicators. Francophones were more likely to report pain (10.9% vs 9.9%; P = .001) and be physically restrained (7.3% vs 5.2%; P < .001), whereas a greater proportion of anglophones experienced worsening of depressive symptoms (24.0% vs 22.9%; P = .001). However, quality indicators were generally worse for francophones in Non-Designated facilities, except for pain, which was more commonly reported by francophones in French-Designated facilities. Anglophones were more likely to be physically restrained in French-Designated facilities (6.7% vs 5.1%; P < .001). Conclusions and Implications For francophones, quality indicators tended to be worse in the presence of resident-facility language discordance. However, these findings did not persist after adjusting for individual- and facility-level characteristics, suggesting that the disparities observed at the population level cannot be attributed to linguistic factors alone.

Coup d’œil sur la recherche : Qualité et sécurité des soins de longue durée en Ontario [infographie] - Consortium national de formation en santé; van Kemenade, Solange (2022)

Forum on Partnering for Innovative and Collaborative Long-Term Care Solutions for Francophones - Fondation Hélène Tremblay Lavoie Foundation; Reflet Salvéo (Fondation Hélène Tremblay Lavoie Foundation, 2019)
Access to French Language Services, more specifically to long term care beds and specialized dementia care units are not equitable and accessible across the Greater Toronto Area (GTA) and do not meet the specific needs of the Francophones in terms of location and language needs. Based on the goals of laying the foundation for action-oriented public / private / not-for-profit partnerships (social enterprise), better defining the needs of the Francophone community for specialized long-term care, and exploring innovative models that can be adapted to the different needs of the community, Fondation Hélène Tremblay Lavoie Foundation organized a one-day Forum to engage with different stakeholders on November 23, 2018 in Toronto. The one-day Forum ensured that key stakeholders, namely private/public sector, seniors, caregivers, health and social service providers, long-term care homes, retirement homes, financial institutions, developers and governments (LHINs, ministries, GTA municipalities), French Language Services Planning Entities (Reflet Salvéo and Entité 4) and post-secondary educational institutions such as Collège Boréal, Glendon, UOIT, York and Schulich and University of Toronto) came together to discuss on opportunities to - create an awareness of different programs and care models within the French community - facilitate access to and expansion of French health care services and programs for Francophone adults experiencing loss of autonomy - raise funds to support the improvement of long-term care and for an eventual capital project to support building the first bilingual long-term care facility dedicated to serving Francophone adults experiencing loss of autonomy within the GTA. This one-day engagement provided an opportunity for stakeholders the opportunity to make recommendations on moving forward. As such, 13 recommendations have developed for different stakeholders including the Francophone community.

La prise en compte de la langue dans les foyers de soins pour personnes âgées - Forgues, Éric; Gaucher, Charles; Guignard Noël, Josée; Kabano, John; Michaud, Jacques (Institut canadien de recherche sur les minorités linguistiques, 2012)

La prise en compte du français dans l’organisation des services en foyers de soins majoritairement anglophones au Canada - Michaud, Jacques; Forgues, Éric; Guignard Noël, Josée (Minorités linguistiques et société, 2015)
L’accès aux services de santé en français préoccupe grandement les communautés francophones vivant en situation minoritaire. Le présent article offre un survol de l’espace francophone dans les résidences collectives d’aînés du Nouveau-Brunswick, de la Nouvelle-Écosse et de l’Ontario à la lumière d’une recherche exploratoire menée en 2012. L’analyse des données obtenues auprès d’aînés, d’aidants et du personnel, l’examen de la répartition géographique des résidences et de la population d’aînés francophones, ainsi qu’un aperçu du contexte réglementaire encadrant le fonctionnement de ces résidences permettent de définir la problématique pertinente. Des actions en vue d’améliorer la situation sont examinées. Mots-clés : espace francophone, services de santé en français, francophones en situation minoritaire, foyers de soins, résidences collectives, vieillissement de la population

Cognitive health initiative for Francophone seniors in the GTA - Reflet Salvéo; Entité 4 (Options fo Service Models, 2017)

Rapport sur l’accès aux soins de longue durée en français dans la région de Champlain. Sommaire - Réseau des services de santé en français de l’Est de l’Ontario (2020)

Boîte à outils virtuelle de soins culturellement adaptés pour les francophones dans les foyers de SLD - Réseau du mieux-être francophone du Nord de l’Ontario (2022)

Recommandations de l’étude de besoins sur les foyers de soins de longue durée du Nord de l’Ontario - Réseau du mieux-être francophone du Nord de l’Ontario (Réseau du mieux-être francophone du Nord de l’Ontario, 2022)

Recommendations from the Northern Ontario Long-Term Care Homes Needs Study - Réseau du mieux-être francophone du Nord de l’Ontario (Réseau du mieux-être francophone du Nord de l’Ontario, 2022)

Guide de planification et de prestation des soins de longue durée en français. Leçons tirées du pavillon Omer Deslauriers de Bendale Acres et d'autres services de santé en français pour aînés au Canada - Réseau franco-santé du Sud de l’Ontario (2017)

The impact of dementia and language on hospitalizations: A retrospective cohort of long-term care residents - Riad, Karine; Webber, Colleen; Batista, Ricardo; Reaume, Michael; Rhodes, Emily; Knight, Braden; Prud’homme, Denis; Tanuseputro, Peter (BMC Geriatrics, 2020)
Background Hospitalizations carry considerable risks for frail, elderly patients; this is especially true for patients with dementia, who are more likely to experience delirium, falls, functional decline, iatrogenic complications, and infections when compared to their peers without dementia. Since up to two thirds of patients in long-term care (LTC) facilities have dementia, there is interest in identifying factors associated with transitions from LTC facilities to hospitals. The purpose of this study was to investigate the association between dementia status and incidence of hospitalization among residents in LTC facilities in Ontario, Canada, and to determine whether this association is modified by linguistic factors. Methods We used linked administrative databases to establish a prevalent cohort of 81,188 residents in 628 LTC facilities from April 1st 2014 to March 31, 2017. Diagnoses of dementia were identified with a previously validated algorithm; all other patient characteristics were obtained from in-person assessments. Residents’ primary language was coded as English or French; facility language (English or French) was determined using language designation status according to the French Language Services Act. We identified all hospitalizations within 3 months of the first assessment performed after April 1st 2014. We performed multivariate logistic regression analyses to determine the impact of dementia and resident language on the incidence of hospitalization; we also considered interactions between dementia and both resident language and resident-facility language discordance. Results The odds of hospitalization were 39% lower for residents with dementia compared to residents without dementia (OR 0.61, 95% CI 0.57–0.65). Francophones had lower odds of hospitalization than Anglophones, but this difference was not statistically significant (OR 0.91, 95% CI 0.81–1.03). However, Francophones without dementia were significantly less likely to be hospitalized compared to Anglophones without dementia (OR 0.71, 95% CI 0.53–0.94). Resident-facility language discordance did not significantly affect hospitalizations. Conclusions Residents in LTC facilities were generally less likely to be hospitalized if they had dementia, or if their primary language was French and they did not have dementia. These findings could be explained by differences in end-of-life care goals; however, they could also be the result of poor patient-provider communication.

Données sur les soins de longue durée en français-Équipe Santé Ontario du Grand Fleuve - Santé Ontario; Réseau des services de santé en français de l'Est de l'Ontario; Santé Canada (2022)

Practice # 3: The Pavillon Omer Deslauriers: A Francophone Unit at Bendale Acres (Ontario) - Savard, Jacinthe; Savard, Sébastien; van Kemenade, Solange; Benoît, Josée; Buhay, Corrina; Youbi, Sara; Kubina, Lucy-Ann (2021)

Expériences en foyers de soins de longue durée et enjeux linguistiques en Ontario : Perspectives d’aîné·es francophones, de proches aidant·es, d’intervenant·es et de gestionnaires. Rapport de recherche - van Kemenade, Solange; Benoît, Josée; Bouchard, Louise; Sauvé-Schenk, Katrine; Savard, Jacinthe (Chaire de recherche de l’Université d’Ottawa et de l’Institut du savoir Montfort sur la santé des francophones de l’Ontario (2019-2024), Université d’Ottawa, 2025)
L’étude rapportée dans ce rapport visait à cerner la disponibilité de services en français dans les FSLD, leur accès, ainsi que l’impact de barrières linguistiques sur la santé et le bien-être, la qualité et la sécurité de soins à partir des perspectives des gestionnaires, des intervenant·es et des personnes résidant dans un FSLD ou de leur proche aidant·e. Elle cherchait également à explorer les variations dans l’offre de services en français en fonction du statut linguistique des foyers, qu’ils soient à caractère francophone, désignés, identifiés ou non identifiés. Ce rapport intégral présente des résultats détaillés, accompagnés de plusieurs citations de participants.

Expériences en foyers de soins de longue durée et enjeux linguistiques en Ontario : Perspectives d’aîné·es francophones, de proches aidant·es, d’intervenant·es et de gestionnaires. Rapport de synthèse - van Kemenade, Solange; Benoît, Josée; Bouchard, Louise; Sauvé-Schenk, Katrine; Savard, Jacinthe (Chaire de recherche de l’Université d’Ottawa et de l’Institut du savoir Montfort sur la santé des francophones de l’Ontario (2019-2024), Université d’Ottawa, 2025)
L’étude rapportée dans ce rapport de synthèse visait à cerner la disponibilité de services en français dans les FSLD, leur accès, ainsi que l’impact de barrières linguistiques sur la santé et le bien-être, la qualité et la sécurité de soins à partir des perspectives des gestionnaires, des intervenant·es et des personnes résidant dans un FSLD ou de leur proche aidant·e. Elle cherchait également à explorer les variations dans l’offre de services en français en fonction du statut linguistique des foyers, qu’ils soient à caractère francophone, désignés, identifiés ou non identifiés. Ce rapport de synthèse en décrit les principaux constats, accompagnés de quelques citations de participants.